Simple tree pattern matching for trees in the prefix bar notation - Lahoda, Jan; Žd’árek, Jan (Discrete Applied Mathematics, 2014)
A pushdown automata based algorithm for searching all occurrences of a tree pattern in a rooted directed labelled ordered subject tree is presented. The algorithm allows tree pattern matching with don’t care symbols and with multiple patterns. The subject tree may be for example an abstract syntax tree of a compiler or validating source text editor. Further, a construction and practical evaluation of a simulation algorithm of pushdown automata based tree pattern matching is described.